Теоретичні аспекти венчурної діяльності корпорацій - Кузнецова, І. С. (Видавництво Національного університету «Львівська політехніка», 2007)
Досліджено інститут венчурних інвестицій корпорацій. Автором виокремлено, This article is devoted to searching the problem of institute of corporations venture investment. The author suggests an approach to discovering motives and functions of venture activity corporations.